Advancements in sunflower multiparental population phenotyping for Verticillium Wilt using UAV-based multispectral imagery - Dominguez, Matías; Colombo, Denis Nahuel; Dillchneider Loza, Alexandra; Lavandera, Javier Eduardo; Corro Molas, Andres Ezequiel; Troglia, Carolina Beatriz; Paniego, Norma Beatriz (International Sunflower Association, 2024)
Poster y resumen